Gradient microstructure and mechanical properties of Ti-6Al-4V titanium alloy fabricated by high-frequency induction quenching treatment. (October 2022) - Jian, Shichao; Wang, Jiangxiong; Xu, Dan; Ma, Rui; Huang, Chaowen; Lei, Min; Liu, Dan; Wan, Mingpan
Graphical abstract: Highlights: A gradient microstructure was successfully fabricated by high-frequency induction quenching treatment (HFIQT). Such a gradient microstructure is a result of the temperature gradient developed during induction heating. The Ti-6Al-4 V alloy with gradient microstructure produces an attractive strength-ductility synergy. The mechanical properties are noticeably better than those obtained with conventional treatments. Abstract: A gradient microstructure was successfully fabricated by high-frequency induction quenching treatment (HFIQT) to improve the mechanical behavior of Ti-6Al-4V alloy in this work. Microstructural evolution was systematically characterized by electron backscattered diffraction and transmission electron microscopy. The results showed that the gradient microstructure of the alloy after HFIQT and aging varied from a fine αs lamellae decomposed from α′-martensite at the surface layer to a bimodal microstructure at the center. Moreover, the alloy with gradient microstructure presents an optimal strength-ductility synergy. The tensile test results showed that a best strength plastic product UT of 12433.1 MPa·%, an ultimate strength of 1231 MPa and an elongation of 10.1 % were obtained after HFIQT for 5.2 s and aging at 400 °C for 6 h. The tensile strength of the alloy aged at 400 °C markedly increased with the increase in soaking time from 5.1 to 5.3 s during HFIQT. Meanwhile, the tensile strength of the alloy slightly increased with the decrease in aging temperature from 550 to 400 °C during HFIQT. Surprisingly, the elongation of the alloy also increased with decreasing aging temperature. The effects of the gradient microstructure characteristic on strength and ductility of the Ti-6Al-4V alloy were discussed.